Islam and The Issue of Poverty: Theological Reflection and Social Transformation in Muslim Society - Binnabie, Ahmad Iqtada; Sutrisno, Edi (Program Studi Manajemen Zakat dan Wakaf, 2025)
In the context of the continuously evolving issue of poverty and the increasingly complex global challenges, Islamic teachings offer a paradigm of social justice through wealth redistribution, which is manifested in the practices of zakat, alms (ṣadaqah), and philanthropy as a transformative solution. This study aims to analyze the role of theological reflection and philanthropic practices in poverty alleviation within contemporary Muslim societies comprehensively. The method used is a literature review and primary text analysis by referring to the Qur’an and Hadith as the main sources to reveal the values of justice and social responsibility contained in Islamic teachings, as well as to examine their practical relevance in the context of the modern economy. The results of the study show that the concepts of zakat and alms, as stated in Surah At-Taubah and Surah Al-Baqarah, provide a strong normative foundation for wealth redistribution and the reduction of social inequality. Furthermore, theological reflection in Islam encourages empathy and solidarity among Muslims, as evidenced by the sayings of Prophet Muhammad (peace be upon him), which emphasize the importance of mutual assistance in alleviating the burden of poverty. This study also reveals that the integration of empirical data and field studies is still needed to measure the actual impact of philanthropy implementation in addressing poverty in the modern era. Thus, the integration of theological values and philanthropic practices proves to have significant potential in alleviating poverty and building a more just, inclusive, and prosperous Muslim society.